The activity of ethanol extract and aquadest of Jati Belanda (Guazuma ulmifolia Lamk) leaves against Candida albicans - Imelda Putri Kusharyati; Muhammad Evy Prastiyanto; Wildiani Wilson; Nala Fidarotul Ulya (Medical Laboratory Analysis and Sciences Journal, 2020)
Fungi are the cause of infection, the development of fungal infections in Indonesia is influenced by environmental conditions so that microbes grow quickly and can increase significantly. Candida Albicans is a fungal disease that infects humans. As a country with a tropical climate, Indonesia has potential biodiversity as a medicine, one of which is Dutch teak (Guazuma ulmifolia Lamk) which has secondary metabolites that kill microbes that can be used as natural antifungals. The purpose of this study was to determine the antifungal activity of ethanol extract and distilled water of Dutch teak leaves on the growth of Candida Albicans. The method used is maceration with ethanol and distilled water solvents. The anti-fungal activity was evaluated by the good diffusion method with SDA media. The results of the antifungal activity of ethanol extract and distilled water of Dutch teak leaves against Candida Albicans were indicated by the formation of an inhibition zone around the wells on Candida Albicans ethanol extract concentrations of 25 mg / mL to 1000 mg / mL 8.6 mm - 15.6 mm, the distilled water extract has not formed a zone of inhibition at all concentrations. The conclusion is that the ethanol extract of Dutch teak leaves can inhibit the growth of Candida Albicans. while the distilled water extract was unable to inhibit the growth of Candida Albicans.